2007
DOI: 10.4310/mrl.2007.v14.n4.a10
|View full text |Cite
|
Sign up to set email alerts
|

Stability conditions on curves

Abstract: Abstract. We study some examples of Bridgeland-Douglas stability conditions on triangulated categories. From one side we give a complete description of the stability manifolds for smooth projective curves of positive genus. From the other side we study stability conditions on triangulated categories generated by an exceptional collection. In the case of the projective line this leads to the connectedness and simply-connectedness of the stability manifold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
117
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 11 publications
1
117
0
Order By: Relevance
“…For a smooth curve C , stability conditions were constructed by Bridgeland [9], and Stab.C / has been described by Macrì [25] and Okada [29]; in Burban and Kreußler [11] the case of singular curves of genus one was considered.…”
Section: Examples Of Stability Conditionsmentioning
confidence: 99%
“…For a smooth curve C , stability conditions were constructed by Bridgeland [9], and Stab.C / has been described by Macrì [25] and Okada [29]; in Burban and Kreußler [11] the case of singular curves of genus one was considered.…”
Section: Examples Of Stability Conditionsmentioning
confidence: 99%
“…The reader who is only interested in the classification of autoequivalences should read the proofs of Lemma 4.1 and Corollary 4.2 and may skip the rest of this section. The case dim(X) = 1 was already studied by E. Macrì [17] and S. Okada [26]. We will see that our result is a natural generalization of the case of curves of genus g ≥ 1 (see equation (1)).…”
Section: The Space Of Stability Conditions Onmentioning
confidence: 62%
“…The (semi)stable sheaves of phase φ ∈ (0, 1) coincide with the (semi)stable vector bundles of slope − cot(φπ) in the sense of Mumford. E. Macrì [17] has shown that for g ≥ 1 the group GL + (2, R) acts free and transitive on Stab(X), i.e.…”
Section: Definition 22 ([7]mentioning
confidence: 99%
“…Then Stab(C) ∼ = H × C (= σ 0 · GL + (2, R)) (see [Bri07,Mac07]), where σ 0 is the stability (Coh(C), −d + √ −1 r) in Example 5.12. Let σ = (P, Z) ∈ Stab(C).…”
Section: Lemma 511 ([Bri07][proposition 53])mentioning
confidence: 99%